Techno-Economic Investigation of Using Solar Energy for Heating Swimming Pools in Buildings and Producing Hydrogen: A Case Study - Almutairi, Khalid; Mostafaeipour, Ali; Baghaei, Negin; Techato, Kuaanan; Chowdhury, Shahariar; Jahangiri, Mehdi; Rezaei, Mostafa; Hosseini Dehshiri, Seyyed Jalaladdin; Goudarzi, Hossein; Issakhov, Alibek (Frontiers in Energy Research, 2021)
Solar energy is a free and environmentally friendly supply of power that has negligible impact on the environment, and it has long been used by humans through different methods. However, solar energy technology would use for heating water for buildings as an alternative resource, which would help reduce CO2 reduction and safe environment. A data analysis was performed using the RETScreen software, and the financial outcomes that were calculated using two methods showed a benefit-to-cost ratio of more than 1, a payback period of 11 years, and a reduction in the cost of greenhouse gas emissions of as much as 562 using Method 1; and a benefit-to-cost ratio of more than 1, a payback period of 15 years, and a reduction in the cost of greenhouse gas emissions of as much as 192 using Method 2. Both methods indicated that this project is economically feasible. The aim of this study was to evaluate the utilization of solar energy for household and commercial purposes. The first goal was to explore the technical, economic, and environmental aspects of using evacuated glass tube solar collectors to heat water in an indoor pool in the building, having an area of 50 m2, in the city of Yazd, Iran. The second goal was to evaluate the amount of hydrogen that can be obtained from the installation photovoltaic systems in the province. The results also showed that this project will decrease greenhouse gas emissions by 142 ton-CO2 over 20 years of the useful life of a collector, thereby indicating the possible significant role of such collectors in the reduction of greenhouse gas emissions. Furthermore, the findings indicated that installing a single X21-345 photovoltaic system with a performance rate of 20% can result in the production of 2.1 kg of hydrogen annually.